The verification of the usability of the online Indares.com system in collecting data on physical activity - pilot study [Ověření využitelnosti online systému Indares.com pro sběr dat o pohybové aktivitě - pilotní studie] - Josef Mitáš; Michal Kudláček; Lucie Engelová; Jiri Stelzer; Filip Křen; Karel Frömel; František Chmelík (Palacky University, 2008)
In order to reduce the increase of obesity and an inactive healthy lifestyle in the population, we are seeking means which would enhance a change in physical activity behavior worldwide. Information technologies, especially the internet, are among these means. Research has shown internet intervention to be effective in enhancing health in the population. The aim of the pilot study is to verify the usability of the online Indares.com system in collecting data on physical activity (PA) and at the same time to analyze a possible use of the system for intervention programs. The verification of the Indares.com system was carried out in the spring term (from January to May 2008) in a sample of 114 students at Valdosta State University who recorded their PA regularly into the system. The study analyzed the data from the first 12 weeks of the semester. The results show that the Indares.com system is an effective tool for the online collection of data on PA in its users and that the recorded data can be used for research purposes. Furthermore, the obtained information suggests that the Indares.com system can be used in internet intervention programs. [Ve snaze zmírnit trend nárůstu obezity a inaktivního způsobu života populace jsou celosvětově hledány prostředky, které by přispěly k žádoucí změně pohybového chování lidí. Mezi tyto prostředky patří moderní informační technologie, zejména internet. Dosavadní výzkumy spíše potvrzují efektivnost internetových intervencí zacílených na zdraví populace. Cílem této pilotní studie bylo ověřit praktickou využitelnost internetové aplikace Indares.com ke sběru dat o pohybové aktivitě (PA) a současně analyzovat možnosti využití systému pro intervenční programy. Ověřování systému Indares.com bylo uskutečněno během jarního semestru (leden až květen 2008) na 114 studentech Valdosta State University, kteří svou PA pravidelně zapisovali do systému. V této studii byla vyhodnocena data z prvních 12 týdnů semestru. Z výsledků vyplývá, že systém Indares.com je vhodným nástrojem pro online sběr dat o PA uživatelů a zaznamenaná data jsou využitelná pro výzkumné účely. Získané informace dále naznačují, že systém Indares.com bude využitelný v internetových intervenčních programech.]